2015
DOI: 10.2174/1570162x1401151102125319
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Signaling Molecules in Progressive Multifocal Leukoencephalopathy

Abstract: Progressive multifocal leukoencephalopathy (PML) is a debilitating demyelinating disease of the CNS caused by the infection and destruction of glial cells by JC virus (JCV) and is an AIDS-defining disease. Infection with JCV is common and most people acquire antibodies early in life. After initial infection, JCV remains in an asymptomatic persistent state and can be detected by PCR in many tissues including brain. A major question in PML pathogenesis is how the virus reactivates from persistence in HIV-1/AIDS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…In another study, evaluation of HIV‐1/PML clinical samples and non‐PML controls for expression of TNF‐α and its receptor TNFR1 showed an increase in overall expression in PML as measured by western blot and specific induction in bizarre astrocytes and enlarged oligodendrocytes measured by immunohistochemistry as well as a redistribution of the transcription factors NF‐κB and NFAT4 to preferential localization to the nucleus. This is consistent with the activation of this cytokine/transcription factor pathway in PML .…”
Section: Tests Involving Assays On Biopsy or Autopsy Materialssupporting
confidence: 90%
“…In another study, evaluation of HIV‐1/PML clinical samples and non‐PML controls for expression of TNF‐α and its receptor TNFR1 showed an increase in overall expression in PML as measured by western blot and specific induction in bizarre astrocytes and enlarged oligodendrocytes measured by immunohistochemistry as well as a redistribution of the transcription factors NF‐κB and NFAT4 to preferential localization to the nucleus. This is consistent with the activation of this cytokine/transcription factor pathway in PML .…”
Section: Tests Involving Assays On Biopsy or Autopsy Materialssupporting
confidence: 90%
“…We have proposed that proinflammatory cytokines such as those that occur in HIV-1/AIDS reactivate JCV leading to PML (White and Khalili 2011). In support of this, we found that TNF-α and its receptor TNFR1 are upregulated in clinical samples from HIV/PML and immunohistochemistry of PML brain tissue shows redistribution of NF-κB to the nucleus (Wollebo et al 2016). …”
Section: Introductionsupporting
confidence: 54%
“…Due to its many interactions with other proteins, this JCV NF-κB site also constitutes a nexus for JCV regulation by other signaling pathways including the DNA damage response (White et al 2014) and calcium-activated signaling (Wollebo et al 2012), which are mediated by direct interaction of NF-κB p65 with the proteins Rad51 and NFAT4 respectively. The pathological relevance of these proteins is indicated by the observations that Rad51 is barely detectable in normal brain but is robustly induced in HIV/PML brain sections (Darbinyan et al 2007) and that NFAT4 preferentially localizes to the nuclei of oligodendrocytes and bizarre astrocytes in HIV/PML relative to what is observed in non-PML brain sections (Wollebo et al 2016). A further level of complexity is added to this by the finding that NF-κB p65 is subject to epigenetic regulation of its stimulatory effect on JCV activity by acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…From earlier studies, it is known that active NF-κB translocation to the nucleus [ 45 , 46 ] stimulates transcription of NF-κB-dependent genes including both the early and late genes of JCV as described in our earlier studies [ 13 18 , 35 , 36 ]. JCV infection-induced DDR signaling is associated with a large elevation in the expression level of Rad51 protein [ 19 ], which then physically associates with NF-κB and augment its function [ 23 ] and stimulate transcription of JCV early gene expression [ 17 ].…”
Section: Discussionmentioning
confidence: 86%
“…Cells were harvested as we have described [ 13 , 33 , 34 ] except for experiments to measure sumoylation where iodoacetemide (10 mM) was added to the lysis and wash buffers to preserve SUMOylation. Western blots were performed as described [ 33 , 35 , 36 ]. Briefly, 50 μg of protein was resolved by SDS-PAGE, transferred to nitrocellulose, and immunoblotted with primary antibody (1/1000 dilution) and secondary antibody (1/10000 dilution).…”
Section: Methodsmentioning
confidence: 99%